Analisis Kerajinan Sulaman Dalam Estetika Monroe Beardsley (Studi Pada Kerajinan Sulam di Desa Cikunir Kecamatan Mangkubumi Kota Tasikmalaya): Kerajinan Sulaman - Novia Nurbayani (Hastagina : Jurnal Kriya Seni, 2022)
Art is a thing created by humans in which there is an element of beauty, while the art referred to here is craft art. Craft art is a handicraft art with the stage of making it using human hands and special skills and having a usability or function value in everyday life. This study aims to analyze the embroidery craft using the aesthetic theory of Monroe Beardsley, with reference to the formulation of the problem, how is the analysis of embroidery in the aesthetics of Monroe Beardsley?. This research method uses qualitative research with descriptive analysis so that it can describe and analyze related to the object under study. The findings of this study are in the aesthetic analysis of Monroe Beardsley, embroidery includes a combination of unity, complexity, and seriousness. The combination of unity, including a combination that includes line elements, building elements, elements of the feeling of the surface of the material or texture, and elements of color. The complexity of the level of complexity lies in naturalist motifs which display many forms of stylized of flowers, leaves, stalks, pistils and so on. These forms at first glance seem quite simple, but in the system the process has a level of complexity because it requires tenacity, skill and also patience. This seriousness or intensity can be seen from the form it takes. Intensity or seriousness in a work of embroidery Philosophically everything has a relationship with nature so that it has a serious value where the motif is the result of exploration of artificial forms to look real and also beautiful.